Mode of action of the 2-phenylquinoline efflux inhibitor PQQ4R against Escherichia coli - Machado, Diana (2018)
Efflux pump inhibitors are of great interest since their use as adjuvants of bacterial chemotherapy can increase the intracellular concentrations of the antibiotics and assist in the battle against the rising of antibiotic-resistant bacteria. In this work, we have described the mode of action of the 2-phenylquinoline efflux inhibitor (4-(2-(piperazin-1-yl)ethoxy)-2-(4-propoxyphenyl) quinolone - PQQ4R), against Escherichia coli, by studding its efflux inhibitory ability, its synergistic activity in combination with antibiotics, and compared its effects with the inhibitors phenyl-arginine-β-naphthylamide (PAβN) and chlorpromazine (CPZ). The results showed that PQQ4R acts synergistically, in a concentration dependent manner, with antibiotics known to be subject to efflux in E. coli reducing their MIC in correlation with the inhibition of their efflux. Real-time fluorometry assays demonstrated that PQQ4R at sub-inhibitory concentrations promote the intracellular accumulation of ethidium bromide inhibiting its efflux similarly to PAβN or CPZ, well-known and described efflux pump inhibitors for Gram-negative bacteria and whose clinical usage is limited by their levels of toxicity at clinical and bacteriological effective concentrations. The time-kill studies showed that PQQ4R, at bactericidal concentrations, has a rapid antimicrobial activity associated with a fast decrease of the intracellular ATP levels. The results also indicated that the mode of action of PQQ4R involves the destabilization of the E. coli inner membrane potential and ATP production impairment, ultimately leading to efflux pump inhibition by interference with the energy required by the efflux systems. At bactericidal concentrations, membrane permeabilization increases and finally ATP is totally depleted leading to cell death. Since drug resistance mediated by the activity of efflux pumps depends largely on the proton motive force (PMF), dissipaters of PMF such as PQQ4R, can be regarded as future adjuvants of conventional therapy against E. coli and other Gram-negative bacteria, especially their multidrug resistant forms. Their major limitation is the high toxicity for human cells at the concentrations needed to be effective against bacteria. Their future molecular optimization to improve the efflux inhibitory properties and reduce relative toxicity will optimize their potential for clinical usage against multi-drug resistant bacterial infections due to efflux.